Competence approach to teaching physics in high school (Pedagogy of Higher and Secondary Education, 2012)
Forkun N. Competence approach to teaching physics in high school.In the article reviews ways to implement the competence approach in the process of study of physics of senior school pupils.
Keywords: competence approach; physics; senior school; mind map